Improvement of mechanical and biological properties of TiNi alloys by addition of Cu and Co to orthodontic archwires - Aphinan Phukaoluan (2018)
© 2016 CEO The purpose of this study was to investigate improved performances of TiNi in order to promote tooth movement. Special attention was paid to the effect on the clinical properties of TiNi of adding Cu and Co to this alloy. Ti49.4Ni50.6, Ti49Ni46Cu5and Ti50Ni47Co3(at %) alloys were prepared. Specimens were cold-rolled at 30% reduction and heat-treated at 400 °C for 60 min. Then, the test results were compared with two types of commercial archwires. The findings showed that superelasticity properties were confirmed in the manufactured commercial alloys at mouth temperature. The difference of stress plateau in TiNi, TiNiCo and commercial wires B at 25 °C changed significantly at various testing temperatures due to the combination of martensite and austenite phases. At certain temperatures the alloys exhibited zero recovery stress at 2% strain and consequently produced zero activation force for moving teeth. The corrosion test showed that the addition of Cu and Co to TiNi alloys generates an increase in corrosion potential (Ecorr) and corrosion current densities (Icorr). Finally, we observed that addition of Cu and Co improved cell viability. We conclude that addition of an appropriate amount of a third alloying element can help enhance the performances of TiNi orthodontic archwires.